2022
DOI: 10.3390/insects13090801
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Fatty Acid Profiles of Hermetia illucens Larvae Fats by Dietary Enrichment with Different Oilseeds: A Sustainable Way for Future Use in Feed and Food

Abstract: Edible insects such as the black soldier fly Hermetia illucens L. represent a potential and sustainable source of nutrients for food and feed due to their valuable nutritional composition, which can be modulated through dietary enrichment. The high content of saturated fatty acid (FA) of Hermetia illucens larvae fats can be modulated through dietary enrichment as a result of adding vegetable oils in the rearing substrate. Therefore, the present research aims to highlight the effects of a 10% addition of vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…The composition of the BSFL oil was very similar to the values reported previously [ 15 ]. Although the composition of BSFL can be manipulated [ 17 , 18 , 19 , 20 ], the conditions of rearing and dietary substrate used in commercial production of BSFL are tightly controlled as part of a quality assurance program with the aim of yielding products with a specific and consistent nutrient profile.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of the BSFL oil was very similar to the values reported previously [ 15 ]. Although the composition of BSFL can be manipulated [ 17 , 18 , 19 , 20 ], the conditions of rearing and dietary substrate used in commercial production of BSFL are tightly controlled as part of a quality assurance program with the aim of yielding products with a specific and consistent nutrient profile.…”
Section: Resultsmentioning
confidence: 99%
“…The main fatty acid present in BSFL oil is lauric acid (C12:0), averaging 42.4% of total fatty acids, with myristic (11.0%), palmitic (13.7%), oleic (13.9%), and linoleic (16.2%) acid representing other fatty acids present at large quantities [ 15 ]. It should be noted that the fatty acid composition of BSFL oil can be easily modulated by using different rearing diets to achieve specific targeted fatty acid composition, although lauric acid typically remains present at high concentrations [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that the intake of an HFD led to fat source-specific shifts in the fatty acid pattern of D. melanogaster , implying an efficient absorption of the dietary FAs. This may be relevant in the context of the production of edible insects used as food and feed [ 63 ] because it allows one to modulate the FA pattern of the insects via the choice of an appropriate dietary fat source. A remarkable exception was the long chain unsaturated FAs DHA and EPA (C20 and C22), which are present in high concentrations in FO.…”
Section: Discussionmentioning
confidence: 99%
“…This ability to convert waste into protein makes BSF production an attractive solution for reducing waste and increasing the sustainability of animal feed production. Additionally, the larvae can be raised in a closed system, reducing the risk of environmental contamination and promoting more efficient use of resources [ 4 , 20 , 21 ]. The use of different botanical waste products as feed for BSF larvae can significantly affect their growth performance, conversion efficiency, and larval quality.…”
Section: Introductionmentioning
confidence: 99%